Exploratory Examination of How Race and Criminal Record Relate to Housing Instability Among Domestic Violence Survivors. Issue 21 (November 2022) - Engleton, Jasmine; Sullivan, Cris M.; Hamdan, Noora
Housing instability is a critical concern in the United States, and domestic violence (DV) survivors are a group at high risk for experiencing housing instability or of becoming unhoused. Prior research has also identified having a criminal record (CR) as being a major barrier to obtaining stable housing, and this is truer for Black and Latinx people compared to their White counterparts. No study has examined whether comparable trends exist among survivors of DV, a group also at elevated risk of having a CR, sometimes related to their experience of abuse. The current exploratory study included 305 unhoused or unstably housed female DV survivors who had sought out DV support services. Multivariate regressions explored if survivor race and CR were separately linked to greater housing instability. CR was then explored as a potential moderator in the relation between race and housing instability. Results revealed that DV survivors with a CR faced greater housing instability than those without a CR, Black and Latina survivors experienced greater housing stability than did White survivors, and CR did not moderate the relation between race and housing instability. The racial differences were unexpected and are discussed in light of methodological limitations. This is the first study to date to explore the role of CR possession on housing instability for DV survivors.